Kérdőjel - A Szegedi Televíziós Ifjúsági Érdekvédelem Egyesület műsora
102nd issue, Alliance Française de Szeged, friendship and love, activities of Soros Foundation, music band "Pál utdai fiúk", quiz competition for higher education students